Rodrigo's Portent: California and the Coming Neocolonial Order - Richard Delgado (Washington University Law Review, 2010)
Through the style of a fictional narrative, this paper demonstrates how colonialism is starting to supplant race as an organizing principle, enabling whites to maintain control in the face of demographic change. The paper argues that qualitative concerns, as well as numbers and statistics, supported this thesis and that California was beginning to take on the ―feel of a neocolonial society. The argument, on the basis of several kinds of evidence, is that seeing California in those terms better explain events than does race and racial competition. The paper presentts an argument for a gestalt shift and posits that doing so would offer a better lens for understanding events in a complex state.
Keywords: Prisoners -- California; Prisons -- California; Recidivism -- California; Restorative justice